Acquisition of a Transparent Gender System: A Comparison of Italian and Croatian - Velnić, Marta (Frontiers in Psychology, 2020)
Gender transparency is considered a key facilitator for early acquisition of this category. Here, we compare the acquisition of the gender system of two transparent systems, Italian and Croatian. The study focuses on the different degrees of transparency between the two languages by taking into account their extended nominal paradigms. We have conducted an adjective elicitation task on a total of 60 monolingual Italian and Croatian children divided in two age groups (Italian=3;0 and 3;10, Croatian= 2;10 and 4;2). The results reveal that the Italian gender system is mastered already by the youngest child (age=2;6) and that the two gender values are acquired simultaneously. However, the Croatian children show a significant difference in the error ratio between the two age groups, which indicates that the gender system is not yet acquired in the younger group (average age=3;0). Additionally, the results suggest that feminine is the first gender to be mastered in Croatian due to the regularity of its paradigm, and that neuter is the most problematic gender for the children, likely due to its lower frequency and syncretism with masculine throughout the case paradigm. This paper adds to the body of research indicating that transparency of the gender system is not merely a binary feature, it underlines the relevance of placing the languages on a continuum with respect to transparency in order to make predictions related to the acquisition of the gender system.